Yersiniabactin produced by Escherichia coli promotes intestinal inflammation through lipid peroxidation and ferroptosis - Wang, Hao; Chen, Bingxun; Xiao, Peng; Han, Dongmei; Gao, Bin; Yan, Yulin; Zhao, Ru; Pan, Tianling; Zhang, Jingsong; Zhou, Meng; Lv, Longbao; Gao, Hong (Frontiers in Microbiology, 2025)
Escherichia coli (E. coli), a major foodborne pathogen, poses significant risks to public health by causing gastrointestinal diseases. Among its virulence factors, Yersiniabactin (Ybt), a siderophore, plays a crucial role in iron acquisition and enhancing intestinal colonization. Despite previous studies highlighting E. coli-Ybt’s involvement in inflammation, its exact mechanisms remain unclear. This study investigates how Ybt contributes to intestinal inflammation through ferroptosis, using both in vitro and in vivo models. Our findings demonstrate that Ybt promotes oxidative stress, lipid peroxidation, inflammation, and iron accumulation in intestinal epithelial cells, leading to ferroptosis. Mechanistically, Ybt suppresses the Keap1/Nrf2 pathway, amplifying reactive oxygen species (ROS) and activating the TNF/NF-κB pathway, which drives inflammation. Moreover, Ybt induces lipid peroxidation via the arachidonic acid pathway, producing 6-trans-leukotriene B4 (6-transLTB4), which exacerbates inflammation and ferroptosis. Exogenous 6-transLTB4 further intensifies this cascade. Additionally, Ybt disrupts iron efflux by suppressing FPN1 expression, causing excessive intracellular iron accumulation. Using tree shrews as an in vivo model, we confirm that Ybt-induced ferroptosis significantly aggravates intestinal inflammation. These findings underscore the pathogenic role of Ybt in E. coli-induced intestinal injury and highlight ferroptosis as a novel mechanism contributing to gut health disruption. This study provides new insights into the molecular pathways of E. coli infection, with implications for therapeutic strategies targeting ferroptosis in intestinal diseases.